2020
DOI: 10.1007/s10900-020-00883-z
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Development Risks and Protective Factors in Vulnerable Preschool Children from Low-Income Communities in South Africa

Abstract: Age-appropriate early childhood development is greatly influenced by exposure to various mediating and moderating factors. Developmental outcomes cannot be viewed in isolation, but by considering the interaction of the various risks and protective factors that influence early child development. A non-experimental, cross-sectional research design was employed. Data was collected in a low-income community in Gauteng, South Africa. Caregivers with children (n = 276) between the ages of 3 years and 6 years 11 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
(67 reference statements)
1
10
1
Order By: Relevance
“…There has been considerable research over the years that has shown those who experience childhood adversity and grow up in poverty tend to score lower on a wide variety of cognitive tasks (Duncan et al, 2017;Ursache & Noble, 2016). However, many children show resilience in the face of adversity (du Toit et al, 2021); for instance, children from low-income backgrounds in South Africa were found to perform higher than children in HICs countries on executive function tasks (Howard et al, 2020), suggesting untapped cognitive potential that could be further fostered by understanding optimal early learning environments. More research is therefore needed to better understand the complex relationships between the home environment and cognitive development in the early years across a variety of countries and contexts.…”
Section: Early Academic Outcomes In Lmicsmentioning
confidence: 99%
“…There has been considerable research over the years that has shown those who experience childhood adversity and grow up in poverty tend to score lower on a wide variety of cognitive tasks (Duncan et al, 2017;Ursache & Noble, 2016). However, many children show resilience in the face of adversity (du Toit et al, 2021); for instance, children from low-income backgrounds in South Africa were found to perform higher than children in HICs countries on executive function tasks (Howard et al, 2020), suggesting untapped cognitive potential that could be further fostered by understanding optimal early learning environments. More research is therefore needed to better understand the complex relationships between the home environment and cognitive development in the early years across a variety of countries and contexts.…”
Section: Early Academic Outcomes In Lmicsmentioning
confidence: 99%
“…In South Africa, the majority of children live in underserved and disadvantaged communities. These children are at increased risk for communication delay because of poverty, disease and psychosocial hazards (Du Toit, Van Der Linde, & Swanepoel, 2021 ; Samuels et al, 2012 ). In addition, children in low-resource settings are at increased risk of developing healthcare-associated infections (HAIs) because of host factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Swanepoel, 2021;Samuels et al, 2012). In addition, children in low-resource settings are at increased risk of developing healthcare-associated infections (HAIs) because of host factors (e.g.…”
mentioning
confidence: 99%
“…3,4 Outcomes in development should not be viewed in isolation, but with the interactions of the various risks and protective factors that influence early child development. 5…”
Section: Introductionmentioning
confidence: 99%